Dissection of the methyl-CpG binding domain from the chromosomal protein MeCP2. - Nan, X (1993)
MeCP2 is a chromosomal protein which binds to DNA that is methylated at CpG. In situ immunofluorescence in mouse cells has shown that the protein is most concentrated in pericentromeric heterochromatin, suggesting that MeCP2 may play a role in the formation of inert chromatin. Here we have isolated a minimal methyl-CpG binding domain (MBD) from MeCP2. MBD is 85 amino acids in length, and binds exclusively to DNA that contains one or more symmetrically methylated CpGs. MBD has negligable non-specific affinity for DNA, confirming that non-specific and methyl-CpG specific binding domains of MeCP2 are distinct. In vitro footprinting indicates that MBD binding can protect a 12 nucleotide region surrounding a methyl-CpG pair, with an approximate dissociation constant of 10(-9) M.